SISTEM INFORMASI PENGARSIPAN SURAT MASUK DAN SURAT KELUAR BERBASIS WEB PADA FAKULTAS EKONOMI UNIVERSITAS SULAWESI BARAT - Cita St Munthakhabah R; Al Qadri Hatta; Reski Idrus Reski (LPPM Universitas Al Asyariah Mandar, 2023)
Developments in technology and information indicate that manual data processing is increasingly showing weaknesses. Because of that, we need a more sophisticated data processing by using a computer. This is necessary to realize the acquisition of information according to the needs of decision makers and those who need it. The purpose of this study was to design and implement a letter filing system at the Information Systems Department using a web programming language. This system has inputs such as Faculty profile data, incoming mail data, outgoing mail data and mail disposition data. This system is also used to process incoming and outgoing mail data in the administration section at the Faculty of Economics, University of West Sulawesi. This system has output in the form of attachments from incoming and outgoing letters. The results of making a web for processing incoming and outgoing mail data indicate that the role of computers in information systems is very important as a support in improving the quality of mail data processing activities. Keywords: Information Systems, Incoming Mail, Outgoing Mail, Web Programming.